Accident Recognition Using Mobile Phone - Kansiz, A. Oguz; Guvensan, M. Amac (IEEE, 2013)
Latest mobile phones bring many advantages to our daily life. These gadgets are usually equipped with multiple sensors, such as cameras, GPS, and accelerometers. The data collected from these sensors are used to develop several applications, such as face recognition, voice recognition, and daily activity analysis. Studies show that many accidents occur during daily activities, and we propose the idea that mobile phones can be used to recognize these accidents. Early intervention may reduce or eliminate the risk of fatal injury during an accident. In this study, we present a new mobile phone application designed for the recognition of small accidents and reporting the incident to appropriate authorities. Our test results show that the proposed system can recognize the events such as falling while walking or running with 99 percent success ratio.
Keywords: Accelerometer; sensor; accident recognition; smart phone; Android; NETWORK; Engineering; Telecommunications